2012
DOI: 10.1109/lpt.2012.2190591
|View full text |Cite
|
Sign up to set email alerts
|

Side-Illumination Fluorescence Dye-Doped-Clad PMMA-Core Polymer Optical Fiber: Potential Intrinsic Light Source for Biosensing

Abstract: A specially designed laser-dye-doped polymer optical fiber (POF) was drawn and investigated experimentally. The cladding of the POF was doped with Rhodamine 640 and pumped with a compact and low-cost 532-nm diode-pumped solid-state laser. By using the side-illumination fluorescence technique, any section along the POF can act as an intrinsic light source. The fluorescence power of the dye-doped POF under side-illumination was improved by more than 10 times by a bending method. With this enhancement, the issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…It was found that bend radius of 1 mm with five turns in the coil facilitated the maximum amount of pump light coupled into the fiber. A cut-back loss measurement was made using this setup, and the propagation loss of the fiber was ~1.3 dB/m at the peak fluorescence wavelength, which was indeed better than that found in a dye-doped clad, all-polymer fiber reported previously with loss of >3 dB/m [2]. The fiber was hydrogen loaded, and a FBG was written into the fiber using the phase mask technique with a 190 nm ArF excimer laser.…”
Section: Fabrication Methodsmentioning
confidence: 64%
See 2 more Smart Citations
“…It was found that bend radius of 1 mm with five turns in the coil facilitated the maximum amount of pump light coupled into the fiber. A cut-back loss measurement was made using this setup, and the propagation loss of the fiber was ~1.3 dB/m at the peak fluorescence wavelength, which was indeed better than that found in a dye-doped clad, all-polymer fiber reported previously with loss of >3 dB/m [2]. The fiber was hydrogen loaded, and a FBG was written into the fiber using the phase mask technique with a 190 nm ArF excimer laser.…”
Section: Fabrication Methodsmentioning
confidence: 64%
“…Also, enabling the epoxy to be fully cured with minimal photobleaching [3] made to the laser dye. The fiber was characterized by a bending side-illumination method described in [2]. An experiment was carried out to find the optimum bend radius and number of turns in the coil.…”
Section: Fabrication Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber-based electronic and photonic devices are soft, ubiquitous, flexible, stretchable, light, and permeable, having the most desired human-friendly features, and thus are ideal to be used for the interface platform between humans and machines, as well as body area network. , In recent years, they have been extensively investigated by our group, including highly durable large strain sensors (up to 60% strain and over 1 million loading cycles), medium to high pressure (50 kPa to 10 MPa) sensors, fiber optic sensors for simultaneous measurement of a few kilopascal pressure and shear force at the human and clothing interface, temperature sensors and sensing networks, humidity sensors, gas sensors, , highly durable and 3D deformable fabric circuit boards, light-emitting devices, and actuators, , among others. These devices have been further investigated for a range of wearable applications including an intelligent footwear system for continuous monitoring of planar pressure distributions, , a monitoring system of contractility of skeletal muscles in motion, compression garments, respiration monitoring, phototherapy, , supercapacitors, self-powered sensors, and so on.…”
Section: Introductionmentioning
confidence: 99%